2022
DOI: 10.3390/life12070979
|View full text |Cite
|
Sign up to set email alerts
|

Non-Inferiority of Sutureless Aortic Valve Replacement in the TAVR Era: David versus Goliath

Abstract: Background: The rapid development of transcatheter treatment methods has made transcatheter aortic valve replacement (TAVR) a feasible alternative to conventional surgical aortic valve replacement (SAVR). Recently, indications for TAVR have been expanded to intermediate- and low-risk patients, although there still remains a portion of ineligible patients. We sought to evaluate and compare our experience with sutureless SAVR and transapical TAVR in the “grey-area” of patients unsuitable for transfemoral access.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The growing population of elderly patients suffering from aortic valve disease highlights the importance of implementing minimally invasive techniques that can reduce ischemia reperfusion injury during aortic valve replacement [ 5 ]. In this regard, SU-AVR and TAVI are both considered promising and less invasive approaches for these patients [ 6 , 7 , 8 ]. Although the use of TAVI in the lower-risk patients is increasingly supported by evidence in the literature [ 29 ], most of the studies which compare TAVI with the standard surgical AVR do not include patients who underwent an SU-AVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing population of elderly patients suffering from aortic valve disease highlights the importance of implementing minimally invasive techniques that can reduce ischemia reperfusion injury during aortic valve replacement [ 5 ]. In this regard, SU-AVR and TAVI are both considered promising and less invasive approaches for these patients [ 6 , 7 , 8 ]. Although the use of TAVI in the lower-risk patients is increasingly supported by evidence in the literature [ 29 ], most of the studies which compare TAVI with the standard surgical AVR do not include patients who underwent an SU-AVR.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, Perceval prosthesis was implanted using the ‘snugger method’, as previously described [ 24 ]. Concomitant procedures were combined with SU-AVR and performed as described in our recent research [ 7 , 11 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were excluded if any of the following criteria were met: (1) reported outcomes of exclusively other SU-AVR [11][12][13][14][15]; (2) grouped outcomes of Perceval with other prostheses in the same cohort [16][17][18][19]; (3) not published in the English language; (4) not published in a peer-reviewed journal; (5) was a conference abstract [20][21][22][23]; and (6) case reports.…”
Section: Exclusion Criteriamentioning
confidence: 99%